A Study on the Effect of Steam Leakage to the Heat Rate of Steam Power Plant - Choi , Y ee Xiong (Universiti Teknologi PETRONAS, 2013)
Leakages in steam lines or components in a steam power plant might not cost a big amount of money during the days when fuel price was low but nowadays, the extra cost due to steam leakage is very significant. Moreover, steam leakage is mostly found on old steam power plant, the additional cost due to steam leakage will cause big loses and the particular steam power plant might have to be shut down. This final year project focuses on the awareness on implications of steam leakage in a steam power plant. The main objective of this project is to identify the impact of steam leakage to the heat rate of the steam power plant. A 5-KW steam power plant in UTP was used to study the effects of steam leakage. Major components of the steam power plant cycle such as the boiler, condenser and turbine were looked into in this project. Steam leakage experiments were conducted using the 5-KW steam power plant. The results showed that steam leaking in the steam power plant would increase the fuel consumption, by as high as 35%.